New approaches to study metal-induced stress in plants - Cia, M. C.; Capaldi, F. R.; Carvalho, R. F. [UNESP]; Gratão, P. L.; Azevedo, R. A. (Springer Nature, 2012)
The contamination of water, soil, and sediments with toxic metals has been and will continue to be a major environmental problem that needs to be dealt with. In more recent years, the studies with metals have concentrated on the antioxidant stress response characterization in a wide range of plant species. The effects of many different metals have been published, but all have consistently addressed very similar problems and investigated basic parameters. These kinds of studies are important as they allow the verification of the sensitivities of different plant species to distinct metals, eventually indicating specific biomarkers to stressful situations. However, metal-induced stress studies need new approaches that are likely to increase our understanding as how these elements affect plant metabolism and to identify the modifications that are needed to improve plant adaptation and tolerance. New techniques that have greatly improved the identification, localization, and quantification of metals within plant tissues have led to the science of metallomics. This advancement in knowledge should eventually allow the characterization of plants used in the process of phytoremediation of soils contaminated with toxic metals. In this chapter, we discuss the use of new techniques and approaches to study the effects of toxic metals and we propose a more integrated action among distinct areas in the field of metallomics and other “omics”.
Keywords: Cytogenetics; Grafting; Heavy metals stress; Metallomics; Proteomics; Signaling